The Influence of Discipline, Self-Efficacy and Motivation on the Employee Performance at CV. IRDH Malang - Binti Abdullah, Isnaeni Ibrahim; Indra Gunawan, Cakti; Hidayat, Imam (International Journal of Management and Business, 2024)
Performance is influenced by discipline, self-efficacy and motivation. The purpose of this research is to determine the influence of discipline, self-efficacy and motivation on the employee performance at CV IRDH Malang. This research uses quantitative methods with data analysis using multiple linear regression. The research results show that discipline has a significant effect on the employee performance of CV IRDH Malang, proven by the results of the T-test, obtained a significant value of 0.000 < 0.05 and t count > t table 4.555 > 1.987. Self-efficacy has a significant effect on the employee performance of CV IRDH Malang, proven by the results of the T-Test, obtained a significant value of 0.012 < 0.05 and t count > t table (2.440 > 1.987). Then, motivation has a significant effect on the employee performance of CV IRDH Malang, proven by the results of the T-test, obtained a significant value of 0.008 < 0.05 and t count > t table (2.740 > 1.987). Simultaneously, discipline, self-efficacy and motivation influence the employee performance of CV IRDH Malang, this is proven by F count > F table, namely 8.786 > 2.71 and the significant value can also be seen as 0.000 < 0.05. CV IRDH Malang needs to create a conducive and comfortable work environment, by building good communication between leadership and staff, as well as holding gatherings at least once per work period.